Laboratory-scale in situ X-ray absorption spectroscopy of a palladium catalyst on a compact inverse-Compton scattering X-ray beamline. Issue 12 (21st October 2021) - Huang, Juanjuan; Deng, Fuli; Günther, Benedikt; Achterhold, Klaus; Liu, Yue; Jentys, Andreas; Lercher, Johannes A.; Dierolf, Martin; Pfeiffer, Franz
Abstract : We presented detailed instrumentation, data acquisition of in situ X-ray absorption spectroscopy (XAS) using an inverse Compton source. We obtained synchrotron-comparable XAS spectra with a time resolution of <5 min per spectrum. Abstract : X-ray absorption spectroscopy (XAS) is one of the most important techniques used for catalyst characterization, and is often conducted under in situ conditions. Such experiments are typically carried out at synchrotrons, despite the significant improvements in laboratory-based XAS systems in recent years. The limited spectral flux density of X-ray tubes restricts these setups to ex situ or in situ experiments conducted over a large time scale, especially for X-ray energies above 15 keV. In this paper, we present an in situ experiment performed on a palladium-based catalyst at the Munich Compact Light Source (MuCLS), a compact synchrotron facility based on inverse Compton X-ray scattering (ICS). Its brilliant, low-divergence, energy-tuneable X-ray beam makes such a compact facility well suited for XAS techniques, especially with in situ experiments. In this study, we investigated a hydrogen-pretreated Pd/C catalyst, which significantly improves the catalytic decarboxylation activity compared to a bare Pd(0)/C catalyst. We measured a series of X-ray absorption near-edge structures (XANES) at the Pd K-edge (24.4 keV), with a time resolution of <5 min per spectrum. The spectral quality achieved is comparable to spectra obtained from synchrotron measurements. The results infer that the formation of α-phase palladium hydride may be the reason for the enhanced performance of the hydrogen-pretreated Pd/C catalyst.